Aty-baty . Aty-baty . One, Two . Аты-баты - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the August 1968 Soviet invasion of Czechoslovakia. Featured in the program: Yevtushenko, Yevgeny Aleksandrovich (Poet); Shenkarev, L.I. (Special Correspondent of the Newspaper "Izvestiia"); Slanskii, Rudol'f (Ambassador of the Czech Republic to Russia) Series description: A program about the Russian army and questions of defense. В передаче обсуждается советское вторжение в Чехословакию в августе 1968 года. В программе участвуют: Евтушенко, Евгений Александрович (Поэт); Шенкарев, Л. И. (Специальный корреспондент газеты "Известия"); Сланский, Рудольф (Посол Чешской Республики в России) Описание серии: Передача о российской армии и вопросах обороны.